Experimental and Numerical Study of Nano-Silica Additions on the Local Bond of Ultra-High Performance Concrete and Steel Reinforcing Bar - Ahad Amini Pishro; Xiong Feng (Civil Engineering Journal, 2017)
Micro-silica is widely used as an additive to cement in producing high performance concrete. This matter is used to enhance the strength and efficiency of concrete. Recently, due to the development of advanced nano-technology, nano-silica has been produced with particle sizes smaller than micro-silica and higher pozzolanic activity. Studies show that addition of nano-silica into cement-based materials improves their mechanical properties. Considering the unique characteristics of nano-silica, it seems that this material can be used in ultra-high performance concrete (UHPC). Therefore, further studies are needed on how the local bond and bond stress of steel reinforcing bar and UHPC containing nano-silica would be effected. In the present study, after preparing the mix designs and proposed specimens, the effects of various parameters on the local bond of steel reinforcing bars and UHPC containing nano-silica were examined by pullout experiments. In this research, we have numerically investigated the bond strength using numerical methods and calibration of the ABAQUS results in addition to its experimental study of ultra-high performance concrete and steel reinforcement. In numerical analysis, the concrete damage plasticity method was used to simulate the nonlinear behavior of concrete and its strain softness. Comparing between numerical and experimental analysis results shows that numerical analysis with high precision can predict the bond stress, bond load, and concrete specimen fracture mode.